Terra Northwest : interpreting people and place / edited by David H. Stratton. - Stratton, David H. 1927- (WSU Press/Washington State University Press, 2007)
"Eleven experts from the United States and Canada explore society, culture, and change in the great, resource-laden Northwest. Essays examine European coastal exploration, American and Canadian comparative development, political and constitutional foundations, economic globalization; gendered and class history, and perspectives on the region's Native American, black, Asian American, and Hispanic citizenry. Included are contributions by Susan Armitage, Kenneth S. Coates, James M. Dolliver, Gordon Hirabayashi, Alvin M. Josephy Jr., Howard R. Lamar, John McClelland Jr., E. Mark Moreno, Quintard Taylor, David J. Weber, and Donald Worster.